ANALISIS DAMPAK INSENTIF PAJAK TERHADAP KEBERLANGSUNGAN USAHA PADA UMKM DI KOTA MADIUN - Erica Putri Rahayu; Isharijadi Isharijadi; Liana Vivin Wihartanti (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2021)
This study aims to determine the knowledge, utilization, application and impact of tax incentives on MSMEs on business continuity. This research was motivated by MSMEs experiencing difficulties with the Covid-19 pandemic. The government provides tax incentive facilities to relieve the community. This tax incentive provides convenience for business actors in carrying out their business activities. This type of research uses descriptive qualitative. The sampling technique used is interactive analysis technique, namely descriptive technique. The samples used were 6 MSMEs including My Optic, Caffe Pool.co, Ishoma, Niored Printing, Photocopy and Print Shops, and the "Maju Lancar" Mie Association. Data collection techniques are interviews, observations and documentation. The results of the study show that 1) Knowledge and utilization of tax incentive policies provided by the government are known and then used and there are those who do not know and have not provided benefits. 2) Obstacles in obtaining tax incentives that there are no obstacles in obtaining tax incentives so that they can be obtained easily. 3) Turnover 1 month before and after the Covid-19 pandemic there is a huge decrease in monthly income. 4) The application of tax incentives to businesses to use facilities as well as possible to support their business activities. 6) The provision of tax incentives is useful to improve the sustainability of businesses that are experiencing a decline in turnover, so that the impact of giving these tax incentives affects business continuity. 7) Changes in business continuity before and after the Covid-19 pandemic, especially in the decrease in turnover from sales every month.